Empathy-Driven Conversation with Chat GPT: Insights from Higher-Ed Arabic Learners - Nely Rahmawati Zaimah; Eko Budi Hartanto (Asalibuna, 2026)
This research examines an empathy-driven approach to Arabic language education, utilizing an AI-powered chatbot, with a focus on enhancing conversational skills among students with diverse learning backgrounds. The study addresses how the chatbot adjusts its interactions to meet emotional and cognitive needs, supporting personalized learning pathways tailored to individual preferences. Methodologically, data were gathered through participant observations and chatbot interactions, analyzing responses to structured prompts and assessing language acquisition progress. Results indicate that students from a traditional Islamic boarding school initially faced challenges in applying conversational Arabic despite strong grammatical knowledge. However, with tailored prompts and supportive interactions from the chatbot, students showed a marked improvement in daily conversational skills, reflected in increasingly spontaneous and contextually appropriate responses observed during later chatbot interaction sessions. The study highlights the crucial role of the chatbot in offering emotional support, providing feedback, and facilitating adaptive learning experiences, thereby fostering a collaborative and inclusive learning environment. This research recommends that scholars explore similar AI-driven frameworks in diverse educational contexts, emphasizing the integration of empathy and personalized learning strategies. Such approaches not only enhance language acquisition but also contribute to broader pedagogical innovations in digital learning environments.   Abstrak Penelitian ini mengkaji pendekatan pembelajaran bahasa Arab berbasis empati dengan memanfaatkan chatbot AI, yang difokuskan pada peningkatan keterampilan percakapan mahasiswa dari latar belakang belajar yang beragam. Studi ini menyoroti bagaimana chatbot menyesuaikan interaksi untuk memenuhi kebutuhan emosional dan kognitif, sekaligus mendukung jalur pembelajaran personal sesuai preferensi individu. Data diperoleh melalui observasi partisipan dan interaksi dengan chatbot, dengan menganalisis respons terhadap instruksi terstruktur serta menilai perkembangan penguasaan bahasa. Hasil menunjukkan bahwa mahasiswa dari pesantren tradisional, pada awalnya mengalami kesulitan dalam menerapkan bahasa Arab percakapan meskipun memiliki pemahaman tata bahasa yang kuat. Namun, dengan arahan yang disesuaikan dan interaksi suportif dari chatbot, para mahasiswa menunjukkan peningkatan nyata dalam keterampilan percakapan sehari-hari, yang tercermin dalam respons yang semakin spontan dan kontekstual selama sesi interaksi chatbot berikutnya. Penelitian ini menegaskan peran penting chatbot dalam memberikan dukungan emosional, umpan balik, dan pengalaman belajar adaptif, sehingga tercipta lingkungan belajar yang kolaboratif dan inklusif. Rekomendasi penelitian ini mendorong para akademisi untuk mengeksplorasi kerangka kerja berbasis AI serupa di berbagai konteks pendidikan, dengan penekanan pada integrasi empati dan strategi pembelajaran personal. Pendekatan semacam ini tidak hanya meningkatkan pemerolehan bahasa, tetapi juga berkontribusi pada inovasi pedagogis dalam lingkungan pembelajaran digital.